O método de tradução de Friedrich Schleiermacher sob o olhar crítico de Johann Albrecht Karl Schäfer - Romão, Tito Lívio Cruz (2013)
The area of research of this thesis is translation of texts about translation theory with commentaries, and it is based on my own translation from German into Portuguese of the essay Ueber die Aufgabe des Uebersetzens by Johann Albrecht Karl Schäfer (1800-1862). The major purpose of this research is to discuss some relevant questions for the field of Translation Theory that arise from the comparison of Friedrich Schleiermacher‘s article On the Different Methods of Translation, initially presented as an academic conference in 1813, and Karl Schäfer‘s essay which was written 26 years later. My translation is preceded by a study on Karl Schäfer‘s biography and on the most important aspects of his work, and by an analysis of the central role of translation in the midst of the German speaking literary scene from German Baroque (around 1600) to Early Romanticism in Germany around 1800. Finally, I present the translation of Karl Schäfer‘s essay for the first time in Portuguese and the commentaries on the translation.